Production of Slime Layer by Staphylococcus Epidermidis Isolated from Hip and Knee Joint Infections during Revision Arthroplasty of Patients in Abn- Sina Hospital in Baghdad - Hadi Abdulah Abd Ali Al-Zuhairi (Journal of Global Pharma Technology, 2018)
This study was carried out to determine the ability of Staphylococcus epidermidis strains to produce slimelayer and biofilm formation during a period of study which extended from1 October, 2016 till 1 October, 2017.Analytic Profile Index (API) system for Staph (Bio-Merieux, France) was used to identify of bacteria to specieslevel. According to Kirby-Bauer (disk diffusion) technique, the antimicrobial susceptibility test was done.Frequency of Staphylococcus epidermidis strains isolated from hip and knee joint infections was higher inmale than female patients, 12(85.7%) vs. 2 (14.3%) (P-value ≤ 0.05).From antimicrobial susceptibility test, themost effective antibiotic was Vancomycin which showed 100% susceptibility rate and the highest resistancerate was to Benzylpenicillin (85.7 %.) followed by Erythromycin and Ampicillin (78.6%). Staphylococcusepidermidis strains were revealed different degrees of resistance towards remaining antibiotics. Out of 14Staphylococcus epidermidis strains under study, 11(78.6%) of Staphylococcus epidermidis strains were slimelayer production, while only 3(21.4%) of Staphylococcus epidermidis strains were non slime layer production(P-value ≤ 0.05) this indicate that Staphylococcus epidermidis strains from Hip and knee infections have theability to format biofilm.Key words: Staphylococcus epidermidis, Hip and knee infections, Osteomyelitis, Slime layer production andBiofilm formation.